1972
DOI: 10.1002/cpt1972136931
|View full text |Cite
|
Sign up to set email alerts
|

Physiologic and clinical effects of chlorpromazine and their relationship to plasma level

Abstract: Physiologic and clinical effects of chlorpromazine and their relationship to plasma levelTen patients suffering from functional psychoses who had not received medication for one month were studied. After investigation before treatment, they received chlorpromazine in liquid form, 100 mg. every 8 hours for 5 to 6 weeks. Testing was carried out on Days 4,8,15,22,29, and 36 or 43 of treatment: (1) Blood samples were taken for chlorpromazine assessment at 0, 2, 4, and 6 hours after the morning dose; (2) blood pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
4

Year Published

1975
1975
1986
1986

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(42 citation statements)
references
References 12 publications
(14 reference statements)
6
32
4
Order By: Relevance
“…This could be interpreted as a mixed effect, a reduction in plasma chlorpromazine concentration by both drugs, together with a further anticholinergic effect possessed by orphenadrine alone. Unlike our previous study (Sakalis et al, 1972), handwriting length was a particularly sensitive measure.…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…This could be interpreted as a mixed effect, a reduction in plasma chlorpromazine concentration by both drugs, together with a further anticholinergic effect possessed by orphenadrine alone. Unlike our previous study (Sakalis et al, 1972), handwriting length was a particularly sensitive measure.…”
Section: Discussioncontrasting
confidence: 62%
“…In a previous study (Sakalis, Curry, Mould & Lader, 1972), we found quite consistently that chlorpromazine concentrations rose during the first 8-15 days of treatment but then fell. Despite this fall, clinical improvement continued as did many physiological effects.…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…Drug concentration in plasma seems to be only weakly correlated to the therapeutic effect (Sakalis et al, 1972;Rivera-Calimlim et al, 1973, 1976, 1978 and this low correlation may reside in the inter--individual differences in CPZ metabolism resulting in different levels of active and inactive metabolites in different patients (Sakalis et al, 1973(Sakalis et al, , 1977Mackay et al, 1974;Sakurai et al, 1975;Phillipson et al, 1977). The high protein binding of CPZ in plasma and the CSF/plasma ratio which seem to be an individual factor (Piafsky et al, 1978;Wode-Helgodt & Alfredson, 1981) may also contribute to this low correlation.…”
Section: Introduction Methodsmentioning
confidence: 99%
“…However, from the eighth to the thirty-sixth day a steady decline in the overall level is seen, although there is still the expected rise and fall during each individual dosage period (Sakalis et al, 1972). Without necessarily quite knowing why, the psychiatrist tends to increase the dose during this time, so that the plasma level may stay elevated, but at a higher dose level.…”
Section: Factors Affecting Drug Concentrations In Plasmamentioning
confidence: 99%